The Oxford handbook of Ancient Nubia - Emberling, Geoff,; Williams, Bruce, 1943- (Oxford University Press, 2020)
"The cultures of Nubia built the earliest cities, states, and empires of inner Africa, but they remain relatively poorly known outside their modern descendants and the community of archaeologists, historians, and art historians researching them. The earliest archaeological work in Nubia was motivated by its role as neighbor, trade partner, and enemy of ancient Egypt. Increasingly, however, ancient Nile-based Nubian cultures are recognized in their own right as the earliest complex societies in inner Africa. As agro-pastoral cultures, Nubian settlement, economy, political organization, and religious ideologies were often organized differently from those of the urban, bureaucratic, and overwhelmingly agricultural states of Egypt and the ancient Middle East. Nubian societies are thus of great interest in comparative study, and are also recognized for their broader impact on histories of the eastern Mediterranean and the Middle East, as well as of neighboring areas"--